Respiratory Pathogens in Children 1 Month to 5 Years of Age Presenting With Undifferentiated Acute Respiratory Distress in 2 District-Level Hospitals in Ghana. (3rd September 2018) - Wilson, Patrick T; Baiden, Frank; Brooks, Joshua C; Giessler, Katie M; Apio, Gavin; Punguyire, Damien; Moresky, Rachel T; Sylverken, Justice; Nyarko-Jectey, Kwadwo; Tagbor, Harry; LaRussa, Philip S
Abstract: Ghanaian children (2176) aged <5 years who presented with undifferentiated acute respiratory distress were tested for respiratory pathogens using a BioFire FilmArray polymerase chain reaction assay. Rhinovirus and/or enterovirus was detected in 36% of the assays, respiratory syncytial virus in 11%, and parainfluenza in 7%. Respiratory syncytial virus and metapneumovirus were detected more frequently in the rainy season than in the dry season. Abstract : A respiratory pathogen was identified in 59% of Ghanaian children who presented with acute respiratory distress. Rhinovirus and/or enterovirus was identified most commonly. Respiratory syncytial virus and metapneumovirus were detected more frequently in the rainy season than in the dry season.